Analysis and Identification of Variables Affecting the Violation of Trademarks in the Field of E-Commerce in Iran - Mohamad Javad Jamshidi; Shirin Armand; Malieh Armand (سیاست نامه علم و فناوری, 2020)
Today, competition in business has led to more and more businesses using the field of electronics in business. Businesses operate in the web environment under their own brand. This trademark leads to the differentiation of the business from other similar businesses. This is done as a result of protecting the business from copying business activities. In the meantime, the issues and challenges of trademarks threaten the business. The present study was conducted to identify the variables affecting trademark infringement in the field of e-commerce. The research is in the category of qualitative research in terms of applied purpose and paradigm, and in terms of methodology, it has used the grounded theory (fundamental theory) research method. The study community is experts in the field of business and lawyers in Kermanshah province. To select the members of the research community, first purposeful sampling method was used and then snowball method was used. The number of participants in the study using the theoretical saturation index was 14. The research findings indicate two main categories resulting from subcategories in trademark infringement in the field of e-commerce, which include; Legal field and business field which includes categories; Legal gaps in trademark infringement in e-commerce law, lack of competent court in dealing with trademark infringement, generality of trademark law, non-inclusion of new changes in the web environment in e-commerce law, problems of trademark principle, threat of rights Exclusivity of the trademark owner, the need to determine the trademark registration processes, the non-inclusion of trademark laws in relation to businesses in the market introduction phase, Loss of trust from consumers and users, reduction of brand credibility, theft of trademarks and trade secrets before legal registration, reduction of business productivity, accumulation of product inventory in the company's warehouse, lack of fair competition between businesses and illegitimate profits for violators. What the research findings indicate is a deep gap in the trademark e-commerce law. This vacuum creates trademark infringement and affects e-commerce businesses. Lack of clear definition of e-commerce laws in Iran and ambiguity in existing laws is itself the biggest factor in trademark infringement. As a result, what is clear is the need to redesign the e-commerce law in Iran and add basic elements in the field of trademarks. Finally, monitoring the strict implementation of laws and maintaining the security of businesses active in this field.